(untitled) (Global Journal of Medical Research, 2020)
Background: Phantom limb pain is a frequent complication after limb amputation, its pathophysiology is complex and includes changes in the peripheral nerve, dorsal root ganglia, spinal cord, cerebral cortex, and thalamus. At this time, there is not an effective drug for treatment and prevention of phantom limb pain. Perineural local anesthetic infiltration has obtained different results in the prevention of phantom limb pain, so we propose to combine an α2 agonist in peripheral nerve block to assess its effectiveness in preventing postoperative pain.